PENINGKATAN KEMAMPUAN MOTORIK HALUS MELALUI KEGIATAN MELIPAT KERTAS ASTURO PADA ANAK KELOMPOK A TK DEWI SARTIKA PULE MODO LAMONGAN - Sutiani, - -; Sholihul Anshori, - - (Al Tadib : Jurnal Ilmu Pendidikan, 2016)
Research on children in TK A Dewi Sartika Pule Modo Lamongan motivated by the fine motor skills were lacking early childhood, especially in terms of ability to hold the paper, put it with the thumb, forefinger, and middle finger, press the crease to the fingertips, folding creases according to the form so that the need for action is through folding. This is necessary because the learning is rarely done. One of the ways to stimulate development through activities asturo paper folding. This study uses a type of action research and qualitative research approaches designed in the form of a repeating cycle consisting of four phases: planning, action, observation and reflection. Data collection techniques in this study using observation data analysis techniques while using descriptive statistical analysis based reflection cycles. The subjects of this study were a group of TK A Dewi Sartika Pule Modo Lamongan the number of 15 children. Based on the data obtained from the first cycle of assembly 1 activity for teachers to get an average value of 50% in the second cycle 3 meeting increased to 94%, the activity children receive an average of 44% in the second cycle 3 meeting increased to 94%, and fine motor skills obtain an average value of 46% at the confluence of 3 increased to 88%. Based on data from the first cycle of this research is continuing on the second cycle because of the success criteria of this action is ≥ 75%. Based on data from the second cycle of action research is declared successful.